The Effect of Kemangi Giving on HIF-1α Expression on DMG Model Rats - Muhammad Iqbal Dasril; Hudila Rifa Karmia; Hirowati Ali (International Journal of Medicine and Health, 2024)
The incidence of diabetes continues to increase worldwide. The state of hyperglycemia during pregnancy can trigger oxidative stress which can result in hypoxic conditions in the tissues characterized by an increase in HIF-1α. Basil which contains antioxidants is expected to reduce the expression of HIF-1α. This study aims to determine the effect of the administration of basil on the expression of HIF-1α in gestational diabetes mellitus model rats. To determine the effect of the administration of basil extract (Ocimum basilicum) on the expression of HIF-1α in gestational diabetes mellitus model rats. This research is experimental research conducted using the post test only control group design method. The research sample used biological material stored from rat RNA that had been induced by streptozotocin 40 mg/kgBB as an animal model of DMG in humans stored in the Biomedical Lab, FK Unand. The results of this study indicate the effect of the administration of basil extract (Ocimum basilicum) on the expression of HIF-1α in gestational diabetes mellitus model rats. Researchers used conventional PCR tools and still manually used ImageJ to look for HIF-1α expression values from electrophoresis results, so the possibility of bias still exists.